MENUMBUHKAN LITERASI ANAK TUMBUHKAN INSPIRASI DI SDN CIKONENG DESA TUGU UTARA KECAMATAN CISARUA KABUPATEN BOGOR - Anwar, Syaiful; Mujito, Mujito; Hardianti, Dwi Tiara (PT. Jurnal Center Indonesia Publisher, 2025)
This activity aims to foster children’s literacy as an effort to enhance inspiration at SDN Cikoneng, Tugu Utara Village, Cisarua Sub-district, Bogor Regency. Children’s literacy is considered a key factor in developing critical and creative thinking skills that can influence their personal and academic growth. Through approaches involving various reading, writing, and discussion activities, this literacy program is expected to encourage students’ motivation and inspiration to further develop their potential. This activity examines various methods applied in literacy practices, such as providing engaging reading materials, training in creative writing skills, and organizing interactive discussions that actively involve students. The expected outcomes include an increased interest in reading and writing, as well as the formation of positive attitudes toward the learning process, which can have a long-term impact on students’ academic and character development. The findings of this study provide insights into the importance of literacy as a means to improve the quality of education at the elementary level, as well as a source of inspiration for students to achieve their best potential.